1975
DOI: 10.1139/v75-030
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Studies. XXVII. Homoenolization of Fenchone. A Mechanistic Study Utilizing C And H Nuclear Magnetic Resonance

Abstract: (1-BuO--1-BuOD, 18S0), C-6(exo and endo), C-8, C-9, and C-10. Both I3C and 2H n.m.r. methods were employed to monitor deuterium incorporation and the particular advantages ofthe latter are illustrated. The relative rates of the five exchange processes were determined directly by 2H n.m.r. in contrast to the earlier homoenolization studies for which the stereoselectivity of exchange was established indirectly. The intermediate homoenolate ion can lead to rearrangement and the rearrangement products have been ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1975
1975
1990
1990

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…4 together with published data for the closely related systems 13 (6), 14 (6), 15 (12), and 16 (20). In our earlier study (12) of fenchone (15) exchange at C-7 was not detected but, in a more recent examination, Werstiuk et al (6) found that slow exchange indeed occurs with a distinct preference for the syn over the anti site even though it would appear that the anti hydrogen is the less hindered. However, the rate of syn exchange was found to be the same as that in 13 for which the syn-and anti-7 hydrogens are in similar steric environments but exhibit a synlanti preference of 5 : 1.…”
Section: Hid Exchange Experimentssupporting
confidence: 66%
“…4 together with published data for the closely related systems 13 (6), 14 (6), 15 (12), and 16 (20). In our earlier study (12) of fenchone (15) exchange at C-7 was not detected but, in a more recent examination, Werstiuk et al (6) found that slow exchange indeed occurs with a distinct preference for the syn over the anti site even though it would appear that the anti hydrogen is the less hindered. However, the rate of syn exchange was found to be the same as that in 13 for which the syn-and anti-7 hydrogens are in similar steric environments but exhibit a synlanti preference of 5 : 1.…”
Section: Hid Exchange Experimentssupporting
confidence: 66%
“…Subsequently, a variety of mono-and bicy-ring-expanded product was not detected (2) indiclicketones,eachhavinggem-dimethylsubstitution cating that 2 4 3 is a minor process in t-BuO-/ at the a-methylene positions, has been found to t-BuOH at 185°C. Analogous results were found for exhibit a-methyl HID exchange in deuteriated base the other examples and, in all cases, the recovery of under homoenolization conditions (3)(4)(5)(6)(7). These starting material and/or rearranged products arisexamples include the tetramethylcycloalkanones ing through homoenolization at skeletal carbons was high.…”
supporting
confidence: 77%
“…Consequently a series of measurements at 155°C was performed to permit an improved assessment of t h e relative rates at the different sites in ketones 1-3. Deuterium incorporation was monitored by examination of the 'Hmr spectra of the deuterated products (4). Analysis of the proton spectra of 1-3 aided by the use of the Eu(fod), shift reagent and spin decoupling allowed unambiguous assign~nents of the signals in the 'H spectra.…”
mentioning
confidence: 99%